A Literature Review of the Poly Herbo-Mineral Formulation (Vellai Venkaiyah Kulikai) that Is Commonly Used in Siddha Medical System of the Sri Lanka - Vinotha Sanmugarajah; Mathangy Gowreeshan (Research Center for Rational Use of Drugs (RCRUD), 2021)
A poly herbo-mineral preparation (Pill) (Vellai Venkaya Kulikai) which is used for treating painful menstruation, gastrointestinal disorders and abdominal pain in Siddha Medicine which is one of the traditional medical systems in Sri Lanka. Based on references, the preparation method of Vellai Venkaya Kulikai (VVK), which is mentioned in the Siddha Book of Pararajasekaram (Karppa roga nithanam) is commonly practiced in the health services of the Siddha medical system in Sri Lanka. Therefore, this preliminary step was taken to provide documentary evidence for the therapeutic effects of the ingredients which are used to the preparation of VVK. Data for the review of 28 ingredients were collected from relevant research sources from September 2020 to April 2021. Data entry form was prepared based on the characteristics of the ingredients such as families; morphology; parts used; siddha properties; pharmacological actions and phytochemical contents. Among these ingredients, all were identified as 25(89%) herbal, 2(7%) minerals and 1(4%) metal. These herbal ingredients are belonging to 15 families and 5(20%) of the species were found in the family of Umbelliferae. Based on the growth habit, these plant materials were classified as 17(68%) herbs and 9 (36%) species were used as seeds. Among 28 ingredients, siddha properties such as 15(48%) pungent taste, 21(81%) hot potency and 15(80%) pungent efficacy; carminative 17(11%) and stimulant 16(10%) actions and phytochemicals as volatile oil 20(15.87%) were found. Although this study provides the clear information for the therapeutic effects, further scientific studies for VVK and each medicinal ingredient should be performed in future.